Dans l’ombre des ordres : les ordres de chevalerie et les territoires de la collection Gaignières - Pierre Couhault (Les Cahiers de l'École du Louvre)
Chivalric orders occupy a disproportionately large place in François-Roger de Gaignières’ collection. They seem to have been at the heart of many of the scholar’s decisions : his choice to select a particular place, his choice of how to deal with documentation on a particular place. They dictated his perception of certain regions, such as Anjou or Malta. Finally, they undoubtedly influenced the spatial organisation of his cabinet and the intellectual foundations of his geography.